725. Clinical Outcomes of Elderly Individuals Presenting with Acute Respiratory Infections. (26th November 2018) - Bloom, Allison; Suchindran, Sunil; Mcclain, Micah T
Abstract: Background: Elderly individuals experience increased morbidity and mortality from acute respiratory infections (ARI), which are complicated by difficulties defining etiologies of ARI and risk-stratifying patients in order to guide care. A number of scoring tools have been developed to predict illness severity and patient outcome for proven pneumonia, however less is known about the use of such metrics for all causes of ARIs. Methods: We analyzed risk factors, clinical course and major outcomes of individuals ≥60 years of age presenting to the emergency department with a clinical diagnosis of ARI over a 5-year period. Results: Of the enrolled individuals 40 had proven viral infection and 52 proven bacterial infections, but 184 patients with clinically adjudicated ARI (67%) remained without a proven microbial etiology despite extensive workup. Age (71.5 vs. 65.9 years, P < 0.001) and presence of cancer and heart failure were strongly predictive of illness severe enough to require hospital admission as compared with treatment in the outpatient setting. Of those with proven etiology, individuals with bacterial infection were more likely to require hospital and ICU admission ( P < 0.001). When applied to this study, a modified PORT score was found to correlate more closely with clinical outcome measures than a modified CURB-65 ( r, 0.54 vs. 0.39). Jackson symptom scores, historically used for viral illness, were found to inversely correlate with outcomes ( r, −0.34) and show potential for differentiating viral and bacterial etiologies ( P = 0.02). Interestingly, a multivariate analysis showed that a novel scoring tool utilizing sex, heart rate, respiratory rate, blood pressure, BUN, glucose and presence of chronic lung disease and cancer was highly predictive of poor outcome in elderly subjects with all-cause ARI. Conclusion: Elderly subjects are at increased risk for poor clinical outcomes from ARI and their clinical management remains challenging. However, modified PORT, CURB-65, Jackson symptom score, and a novel scoring tool presented herein all offer some predictive ability for all-cause ARI in elderly subjects. Such broadly applicable scoring metrics have the potential to assist in treatment and triage decisions at the point of care. Disclosures: All authors: No reported disclosures.